2007
DOI: 10.1016/j.pbb.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic modulation of binge-like ethanol intake in C57BL/6J mice

Abstract: GABA receptor systems have long been implicated in alcoholism, and GABAergic drugs have demonstrated efficacy in altering alcohol intake in some rodent models. The present study was designed to assess the effects of baclofen, muscimol, and gaboxadol (THIP) in a variation on a new mouse model of binge-like ethanol intake. Three hours into their dark cycle, male and female C57BL/6J mice were given access to a 20% unsweetened ethanol solution for 2 h each day, for four days. On day five, mice received varying dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(114 citation statements)
references
References 35 publications
8
103
3
Order By: Relevance
“…These results are consistent with an accumulating number of experimental data indicating that treatment with GABA B receptor direct agonists or GABA B receptor positive allosteric modulators suppress different alcohol-related behaviors in rats and mice, including alcohol drinking under the 2-bottle choice regimen (Daoust et al, 1987;Colombo et al, 2000Colombo et al, , 2002Colombo et al, , 2003aColombo et al, , 2006Stromberg, 2004;; see however Moore et al, 2007), operant alcohol selfadministration (Anstrom et al, 2003;Janak and Gill, 2003;Besheer et al, 2004;Maccioni et al, 2005Maccioni et al, , 2007Liang et al, 2006;Walker and Koob, 2007; see however Petry, 1997;Czachowski et al, 2006), and cue-induced reinstatement of alcohol seeking behavior (Maccioni et al, 2008a). Focusing on animal models of alcohol's motivational properties, the results of the baclofen experiment included in the present study are in agreement with data demonstrating the suppressing effect of baclofen on (i) extinction responding for alcohol in sP (Colombo et al, 2003b) and Long-Evans (Leite-Morris and rats, and (ii) breakpoint for alcohol in Wistar rats (Walker and Koob, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with an accumulating number of experimental data indicating that treatment with GABA B receptor direct agonists or GABA B receptor positive allosteric modulators suppress different alcohol-related behaviors in rats and mice, including alcohol drinking under the 2-bottle choice regimen (Daoust et al, 1987;Colombo et al, 2000Colombo et al, , 2002Colombo et al, , 2003aColombo et al, , 2006Stromberg, 2004;; see however Moore et al, 2007), operant alcohol selfadministration (Anstrom et al, 2003;Janak and Gill, 2003;Besheer et al, 2004;Maccioni et al, 2005Maccioni et al, , 2007Liang et al, 2006;Walker and Koob, 2007; see however Petry, 1997;Czachowski et al, 2006), and cue-induced reinstatement of alcohol seeking behavior (Maccioni et al, 2008a). Focusing on animal models of alcohol's motivational properties, the results of the baclofen experiment included in the present study are in agreement with data demonstrating the suppressing effect of baclofen on (i) extinction responding for alcohol in sP (Colombo et al, 2003b) and Long-Evans (Leite-Morris and rats, and (ii) breakpoint for alcohol in Wistar rats (Walker and Koob, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…We have previously demonstrated that systemic administration of the GABA B receptor agonist baclofen increased ethanol drinking in C57BL/6J (B6) mice using the limited-access ethanol drinking procedure Drinking in the Dark (DID) (Moore et al, 2007). However, varied response to baclofen is common in the general ethanol intake and self-administration literature.…”
Section: Introductionmentioning
confidence: 99%
“…Mice consume considerable amounts of ethanol with blood ethanol concentrations (BECs) exceeding 100 mg/dl. Since its development, DID has been widely used to test a broad range of pharmacological targets for alcohol use disorders (AUDs) (Gupta et al, 2008; Hendrickson, Zhao-Shea, & Tapper, 2009; Kamdar et al, 2007; Moore et al, 2007; Sparta et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DID was shown to be reduced by intraperitoneal naltrexone doses that did not affect water or sugar-water intake (Kamdar et al 2007). Another group has shown that the GABA B agonist baclofen reduced ethanol DID without affecting water drinking, while two GABA A agonists, THIP and muscimol, reduced drinking nonspecifically (Moore et al 2007). A CRF 1 receptor antagonist also reduced ethanol DID without affecting sucrose drinking (Sparta et al 2008).…”
Section: Selective Breedingmentioning
confidence: 99%